The Effect of Psychoeducation on Self-Efficacy in Elderly People with Diabetes Mellitus - Harniko, Arafanda Maharani Putri; Kustin; Vitaliati, Trisna (LPPM Universitas dr. Soebandi, 2024)
Introduction: Diabetes mellitus is a long-term illness that presents threats to one’s physical health as well, but also has a significant psychological impact on sufferers, as a result of which the ability to increase self-efficacy decreases. Psychoeducation can be chosen as an alternative to help the elderly to form positive coping by increasing their self-efficacy. This study aims to analyze the effect of psychoeducation on self-efficacy in elderly patients with diabetes mellitus in the Jenggawah Community Health Center area. Methods: The method used in this research was a quasi-experimental design using an intervention group and a control group. The sample in this study was 60 elderly people with diabetes mellitus. This research uses a purposive sampling technique. The measuring tool in this research is the Diabetes Management Self-efficacy Scale questionnaire which consists of 18 statements that are valid and reliable. Data analysis used the Wilcoxon and Mann Whitney tests. Results: The results of the Wilcoxon Test statistical analysis were obtained in the pre-post test of the intervention and control groups, p-value 0.000 < 0.05. The Mann Whitney test showed a p-value of 0.000 < 0.05 indicating that there was an influence of providing psychoeducation on Self Efficacy in elderly people with diabetes mellitus at the Jenggawah health center. Conclusions: Psychoeducational activities can be an alternative intervention used by Public Health Center to increase motivation and also information to patients about the importance of Self Efficacy in empowering diabetes mellitus.